Physician Burnout and Timing of Electronic Health Record Use - Micek, Mark A.; Arndt, Brian; Tuan, Wen-Jan; Trowbridge, Elizabeth; Dean, Shannon M.; Lochner, Jennifer; Sampene, Emmanuel; Pandhi, Nancy (ACI Open, 2020)
Background Rates of burnout among physicians have been high in recent years. The electronic health record (EHR) is implicated as a major cause of burnout.Objective This article aimed to determine the association between physician burnout and timing of EHR use in an academic internal medicine primary care practice.Methods We conducted an observational cohort study using cross-sectional and retrospective data. Participants included primary care physicians in an academic outpatient general internal medicine practice. Burnout was measured with a single-item question via self-reported survey. EHR time was measured using retrospective automated data routinely captured within the institution's EHR. EHR time was separated into four categories: weekday work-hours in-clinic time, weekday work-hours out-of-clinic time, weekday afterhours time, and weekend/holiday after-hours time. Ordinal regression was used to determine the relationship between burnout and EHR time categories.Results EHR use during in-clinic sessions was related to burnout in both bivariate (odds ratio [OR] = 1.04, 95% confidence interval [CI]: 1.01, 1.06; p = 0.007) and adjusted (OR = 1.07, 95% CI: 1.03, 1.1; p = 0.001) analyses. No significant relationships were found between burnout and after-hours EHR use.Conclusion In this small single-institution study, physician burnout was associated with higher levels of in-clinic EHR use but not after-hours EHR use. Improved understanding of the variability of in-clinic EHR use, and the EHR tasks that are particularly burdensome to physicians, could help lead to interventions that better integrate EHR demands with clinical care and potentially reduce burnout. Further studies including more participants from diverse clinical settings are needed to further understand the relationship between burnout and after-hours EHR use.
Keywords: physician burnout; physician health; electronic health records